ANALISIS PENGEMBANGAN DESAIN PRODUK MINI CONCRETE PUMP DENGAN METODE SUSTAINABILITY - Muchammad Ragil Prawira; Tri Andi Setiawan; Fais Hamzah (Proceedings Conference On Design Manufacture Engineering And Its Application, 2022)
consumers and markets need a new product in order to remain competitive in the industry 4.0 era. One way is to make products that are more environmentally friendly as well as to reduce the impact on the environment in the manufacture of these products. Sustainability is one of the appropriate methods to reduce the negative impact of working on a product on the environment, starting from the selection of materials, the selection of the fabrication process, and the percentage of machine parts that will become waste. The selection of the product that will be used as the initial product or as the object of a redesign is a mini concrete pump with one weakness in the fabrication process which results in too many negative impacts on the environment, one of which is in the selection of materials and the work process carried out. Initial product that has been redesigned creates 2 new designs. From the three designs, a sustainability analysis was applied and it was found that the design that has less impact on the environment based on the Sustainability Analysis analysis includes a carbon footprint of 820 kg CO2e, total energy consumption of 8900 MJ, water acidification of 5 Kg SO2e, and water eutrophication of 0.680 Kg PO4e was found on the mini concrete pump redesign concept 1.